The impact of primary immunization route on the outcome of infection with SARS-CoV-2 in a hamster model of COVID-19 - Barrett, Edward G.; Revelli, David; Bakshi, Chandra Shekhar; Kadish, Alan; Amar, Salomon (Frontiers in Microbiology, 2023)
The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has resulted in over 6.7 million deaths worldwide. COVID-19 vaccines administered parenterally via intramuscular or subcutaneous (SC) routes have reduced the severity of respiratory infections, hospitalization rates, and overall mortality. However, there is a growing interest in developing mucosally delivered vaccines to further enhance the ease and durability of vaccination. This study compared the immune response in hamsters immunized with live SARS-CoV-2 virus via SC or intranasal (IN) routes and assessed the outcome of a subsequent IN SARS-CoV-2 challenge. Results showed that SC-immunized hamsters elicited a dose-dependent neutralizing antibody response but of a significantly lower magnitude than that observed in IN-immunized hamsters. The IN challenge with SARS-CoV-2 in SC-immunized hamsters resulted in body weight loss, increased viral load, and lung pathology than that observed in IN-immunized and IN-challenged counterparts. These results demonstrate that while SC immunization renders some degree of protection, IN immunization induces a stronger immune response and better protection against respiratory SARS-CoV-2 infection. Overall, this study provides evidence that the route of primary immunization plays a critical role in determining the severity of a subsequent respiratory infection caused by SARS-CoV-2. Furthermore, the findings suggest that IN route of immunization may be a more effective option for COVID-19 vaccines than the currently used parenteral routes. Understanding the immune response to SARS-CoV-2 elicited via different immunization routes may help guide more effective and long-lasting vaccination strategies.